EPIDEMIOLOGY OF POST-COVID SYNDROME - Marić, Gorica; Pekmezović, Tatjana; Jovanović, Aleksa (Medicinski podmladak, 2023)
As per the World Health Organization’s (WHO) definition, post-COVID syndrome or long COVID refers to the persistence or emergence of new symptoms three months after the initial infection with the SARS-CoV-2 virus (severe acute respiratory syndrome coronavirus 2), and lasting for a minimum of two months, while excluding alternative diagnoses. The precise mechanisms responsible for the development of long COVID19 symptoms have yet to be fully understood. The prevalence of post-COVID syndrome exhibits considerable variation, mostly influenced by factors like as study design, study population, and the specific case definition employed in the study. Based on some estimations, a minimum of 10% of those exhibiting a severe clinical manifestation of SARS-CoV-2 viral infection are likely to have post-COVID syndrome. This condition is characterized by multisystemic involvement, presenting a diverse spectrum of symptoms that impact several bodily systems, including but not limited to the respiratory, cardiovascular, musculoskeletal, neurological systems and skin. The prevailing manifestations of prolonged COVID-19 encompass fatigue, dyspnea, and cognitive impairment. Nonetheless, a spectrum of over 200 distinct symptoms have been documented, which can significantly impede the day-to-day capabilities of those afflicted with the condition. Based on data derived from both the United States and Europe, it has been shown that the incidence of long COVID syndrome has a greater frequency among the female population and individuals afflicted with chronic conditions. Considering the global prevalence of individuals affected by the SARS-CoV-2 virus, it is imperative to conduct ongoing epidemiological surveillance to gain a consistent understanding of the current situation. Additionally, it is crucial to perform research, primarily utilizing representative population samples, to enhance our understanding of risk factors and identify potential preventive measures. This knowledge would also contribute to the identification of population groups with a higher susceptibility to the onset of post-COVID syndrome, which holds significant value in comprehending the enduring consequences of the COVID-19 pandemic.